Impact of insecticide resistance on malaria vector competence: a literature review - Pierre Fongho Suh; Emmanuel Elanga-Ndille; Magellan Tchouakui; Maurice Marcel Sandeu; Darus Tagne; Charles Wondji; Cyrille Ndo (Malaria Journal, 2023)
Abstract Since its first report in Anopheles mosquitoes in 1950s, insecticide resistance has spread very fast to most sub-Saharan African malaria-endemic countries, where it is predicted to seriously jeopardize the success of vector control efforts, leading to rebound of disease cases. Supported mainly by four mechanisms (metabolic resistance, target site resistance, cuticular resistance, and behavioural resistance), this phenomenon is associated with intrinsic changes in the resistant insect vectors that could influence development of invading Plasmodium parasites. A literature review was undertaken using Pubmed database to collect articles evaluating directly or indiretly the impact of insecticide resistance and the associated mechanisms on key determinants of malaria vector competence including sialome composition, anti-Plasmodium immunity, intestinal commensal microbiota, and mosquito longevity. Globally, the evidence gathered is contradictory even though the insecticide resistant vectors seem to be more permissive to Plasmodium infections. The actual body of knowledge on key factors to vectorial competence, such as the immunity and microbiota communities of the insecticide resistant vector is still very insufficient to definitively infer on the epidemiological importance of these vectors against the susceptible counterparts. More studies are needed to fill important knowledge gaps that could help predicting malaria epidemiology in a context where the selection and spread of insecticide resistant vectors is ongoing.